The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1016/j.ijhydene.2015.02.112
|View full text |Cite
|
Sign up to set email alerts
|

Composite-alumina-carbon molecular sieve membranes prepared from novolac resin and boehmite. Part I: Preparation, characterization and gas permeation studies

Abstract: Supported composite alumina-carbon molecular sieve membranes (c-CMSM) were prepared from in house prepared novolac phenolic resin loaded with boehmite nanoparticles in a single dipping-drying-carbonization step. A porous a-alumina tube support was dipped into a N-methyl-2-pyrrolidone solution containing polymerized novolac resin loaded with boehmite, subsequently dried at 100 o C and carbonized at 500 o C under nitrogen environment. The structure, morphology and performance of the membranes were examined by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 52 publications
(20 citation statements)
references
References 37 publications
1
19
0
Order By: Relevance
“…The novolac resin (phenol formaldehyde resin) used as polymeric precursor was synthesized by the acid-catalyzed phenol-formaldehyde condensation [62] as described elsewhere [57]. Briefly, phenol and oxalic acid were placed in a flask fitted with stirrer and a reflux condenser, when the solution reached 80 o C formaldehyde was added drop-wise, the resin was washed with hot water and further dried.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The novolac resin (phenol formaldehyde resin) used as polymeric precursor was synthesized by the acid-catalyzed phenol-formaldehyde condensation [62] as described elsewhere [57]. Briefly, phenol and oxalic acid were placed in a flask fitted with stirrer and a reflux condenser, when the solution reached 80 o C formaldehyde was added drop-wise, the resin was washed with hot water and further dried.…”
Section: Methodsmentioning
confidence: 99%
“…c-CMSMs were also prepared using novolac phenolic resin and boehmite nanoparticles in a single dipping-dryingcarbonization step on top of a a-Al2O3 tubular membrane support; the decrease in performance of the Al-CMSM due to air exposure (aging by adsorption of water), and the changes in the transport properties of the membranes with different activation temperatures for removing water present in the pores were studied using pure gas permeation [57].…”
Section: Introductionmentioning
confidence: 99%
“…Xiao et al [49] reported the preparation of c-CMSMs from Ag + SPAEK; they observed that the silver doped CMSMs exhibited higher CO 2 /CH 4 selectivities (it was attributed to the greater interconnection among the ultramicropores formed by the migration of silver) and permeabilities. Composite alumina-CMSM using phenolic resins resol [40,50], novolac [37,51] and composite alumina-Ag CMSM [52] were for the first time reported by Pacheco Tanaka and Llosa Tanco et al…”
Section: Introductionmentioning
confidence: 93%
“…D.A. Pacheco Tanaka, M. Llosa Tanco et al reported for the first time the preparation of a 7 cm long, 1 cm diameter-supported composite alumina-CMSM from low cost polymer precursors phenolic resins (resol [40,50,52] and novolac [37,51]) on alumina tubes (200 nm pore size) in one dip-dry-carbonization cycle. When only phenolic resin was used during the preparation, the membranes were unselective (presence of defects) because the precursor penetrated excessively in the pores of the alumina support; consequently, additional dip-dry-carbonization cycles were necessary to obtain membranes without defects.…”
Section: Supported Cmsms Prepared By One Dip-dry-carbonization Cyclementioning
confidence: 99%
See 1 more Smart Citation